Thirty years of global warming potential evolution for the Italian dairy cow sector measured by two different metrics - Marco Berton; Giovanni Bittante; Enrico Sturaro; Luigi Gallo (Italian Journal of Animal Science)
This study aimed to provide a comprehensive evaluation of the greenhouse gases (GHG) emission between 1991 and 2021 of both the entire Italian dairy cattle sector (ITA_POP) and the registered Holstein Friesian population only (HF). An attributional cradle-to-farm gate Life Cycle Assessment was performed, including emissions (methane–CH4, nitrous oxide–N2O, carbon dioxide–CO2) due to animal and manure management, feed production, and farm materials. The functional units were 1 year and 1 kg of fat- and protein-corrected milk. We applied 100-year global warming potential (GWP) metric. For 2011–2021 period, we also applied GWP star (GWP*). Data originated from Italian GHG accounting and official milk recording systems. From 1991 to 2021, annual GHG emission of ITA_POP decreased from 20.4 ± 2.7 to 15.5 ± 2.1 Mt CO2e and emission intensity (EI) from 1.90 ± 0.25 to 1.17 ± 0.16 kg CO2e/kg corrected milk. The share of officially registered HF cows in ITA_POP increased from 36 to 70%. The annual emission of HF increased by 32% to 12.2 ± 1.8 Mt CO2e, but its EI decreased by 34% to 1.09 ± 0.16 kg CO2e/kg corrected milk. The accumulation in GHGs in 2011–2021 period due to ITA_POP (100-year GWP) continuously increased. When considering the short lifetime of CH4 (GWP*), the rate of increase in the same years was quite lower, with a flat pattern in the last 5 years. The decrease in CH4 emission is compensating the accumulation of N2O and CO2 from fossil fuels, highlighting the need of considering GHGs lifetime in the estimation of dairy cow sector emissions.